(untitled) (Ameghiniana, 2013)
Abstract. Here we report the discovery of abelisaurid remains from the Bajo Barreal Formation (Cenomanian-Coniacian) from the northern region of Santa Cruz Province, Patagonia, Argentina. The specimen represents the southernmost record of Abelisauridae in South America. It consists of six associated vertebrae, including cervical 10, dorsal 1, an isolated dorsal centrum, and three caudals from the middle portion of the tail. The vertebrae closely resemble those of other derived abelisaurids (e.g., Carnotaurus sastrei Bonaparte, Aucasaurusgarridoi Coria et al.). For example, the cervicals have deep pre- and postspinal cavities, hypertrophied epipophyses, and a dorsal surface of the neural arch that is clearly delimited from the lateral surface of the diapophysis. Caudal vertebrae exhibit the characteristically fan-shaped transverse processes seen in other abelisaurids. However, some morphological distinctions are recognized when compared with Ilokelesia, Xenotarsosaurus, Carnotaurus, Aucasaurus and Majungatholus. The list of potential synapomorphies of the vertebral column of Abelisauria and Abelisauridae is briefly reviewed. Recent phylogenetic hypotheses on Abelisauridae are discussed. Resumen. RESTOS DE ABELISÁURIDOS (THEROPODA, CERATOSAURIA) DEL SUR DE PATAGONIA. Se informa del hallazgo de restos de un abelisáurido de la Formación Bajo Barreal (Cenomaniano-Coniaciano), del norte de la provincia de Santa Cruz, Patagonia Argentina. Este ejemplar representa el registro más austral de Abelisauridae en América del Sur y consiste en seis vértebras asociadas, incluyendo la cervical 10, la dorsal 1, un centro dorsal aislado y tres caudales de la porción media de la cola. Las vértebras son muy semejantes a las de otros abelisáuridos derivados (Carnotaurussastrei Bonaparte, Aucasaurusgarridoi Coria et al.). Por ejemplo las cervicales tienen profundas cavidades pre- y postespinales, epipófisis hipertrofiadas y la superficie dorsal del arco neural que está claramente delimitada de la superficie lateral de la diapófisis. Las vértebras caudales tienen los característicos procesos transversos en forma de abanico presentes en otros abelisáuridos. Sin embargo se reconocen algunas diferencias morfológicas con Ilokelesia, Xenotarsosaurus, Carnotaurus, Aucasaurus y Majungatholus. Se examina brevemente la lista de potenciales sinapomorfías de Abelisauria y Abelisauridae y se discuten recientes hipótesis filogenéticas de Abelisauridae.